Life Cycle Assessment on Green Building Implementation (MDPI - Multidisciplinary Digital Publishing Institute, 2016)
Greenhouse-gas emissions have become one of the most impacting environmental issues in today's society. A rapidly increasing trend in global CO2emissions particularly since the early nineties (23.64% since 1990) has led to the generation of about 50,000 million tons of CO2-equivalent (eqv) worldwide in 2010. According to mainstream climate experts, the increasing concentration of greenhouse-gases is having a warming effect on the world climate. To slow down global warming, there is a global focus on reducing greenhouse-gas emissions. Life cycle assessment in green building implementation is the focus of this Special Issue.